X^2 - 10x + 8 =0
x^2 - 10 + (-10/2)^2 - (-10/2)^2 + 8 = 0
(x - 5)^2 - 25 + 8 = 0
(x - 5)^2 - 17 = 0
To be honest , this is the final step for this equation. It seems like there is no any suitable answer for this question..
To me , I think the best answer will be the third option.
x - 5 =0
x = 5
2x-10 = 0
2x = 10
x = 5
I guess this answer seems like legit.. So I will choose the third option.
I think it’s 96 I might be wrong sorry if I am
(2x+2)(3x+1)
2x*3x+2x*1+2*3x+2*1
6x^2+2x+6x+2
6x^2+8x+2
Hope this helped
3 1/9 or 3.11 because you get a remainder of 1.